Barriers to Human Papillomavirus Vaccine Series Completion among Insured Individuals in an Integrated Healthcare Setting. (May 2021) - Kamineni, Aruna; Blasi, Paula R; Gundersen, Gabrielle D; Oliver, Malia; Dunn, John B; Galloway, Denise A; Madeleine, Margaret M
Introduction: Infection with certain types of human papillomavirus (HPV) can lead to cervical cancer as well as other cancers in both men and women. However, the requirement for multiple doses may limit the vaccine's effectiveness for cancer prevention. We conducted a pilot study to investigate barriers to HPV vaccine series completion among members of an integrated healthcare system with clinical documentation of only 1 dose. Methods: We surveyed parents or legal guardians of 11-17-year-old girls (n = 10) and boys (n = 18), as well as 18-31-year-old women (n = 20) and men (n = 9), about their reasons for not completing the HPV vaccine series. Results: Most participants (70.2%) were non-Hispanic white. Among parents of children, commonly reported barriers to HPV vaccine series completion included not being aware or informed of the need for additional doses (28.6%), as well as the inconvenience of returning for additional doses (17.9%). Concerns about the HPV vaccine or vaccines in general were more common among parents of girls (30.0%) compared with parents of boys (16.7%). Among adults, barriers to HPV vaccine series completion included the inconvenience of returning for additional doses (31.0%), not being aware or informed of the need for additional doses (10.3%), and forgetting (10.3%). Conclusion: Our findings suggest that clinicians and healthcare systems can play a greater role in promoting awareness of the multiple-dose requirement, addressing vaccine concerns, and increasing opportunistic vaccination in a variety of settings. Increasing these efforts may facilitate HPV vaccine completion and increase its effectiveness in cancer prevention.